Therapeutic efficacy of 5-alkylresorcinol on progression of colorectal cancer by activating HCLS1 and suppressing TLR4/MYD88/NF-κB signaling - Chun Yang; Jun Yang; Heng Li; Wan Fan; Jian Wang (European Journal of Medical Research)
Abstract Background This study investigates the molecular mechanisms underlying the inhibitory effects of 5-alkylresorcinol (5ARs) on colorectal cancer (CRC) growth. Methods HCT116 cells were treated with 15 μmol/L 5ARs for 24 h, with both control and 5ARs-treated groups undergoing transcriptome sequencing. Hub genes were identified through GO and KEGG enrichment analyses. Construct the overexpression plasmid and interference plasmid of HCLS1, and transfect them into HCT116 cells. The impact of HCLS1 on 5ARs' therapeutic effect was evaluated using CCK-8, RT-qPCR, and WB assays. Subsequent animal experiments involved the application of BALB/c nude mice which were injected with HCT116 cells. Three groups were formed: model, 5ARs treatment, and 5ARs treatment with adeno-associated virus (AAV) overexpression plasmid of HCLS1. Tumor growth, Ki67 proliferation, and gene expression were assessed. Results DEGs were primarily enriched in the regulation of myeloid cell differentiation and tight junction, from which the HCLS1 gene exhibiting the highest fold change was selected as the candidate gene. 5ARs significantly increased HCLS1 expression and inhibited TLR4/MYD88/NF-κB (p-p65) expression. Both cellular and animal experiments showed 5ARs and HCLS1 overexpression inhibited HCT116 cell proliferation, tumor growth and TLR4/MYD88/NF-κB (p-p65) expression. Conclusions These findings suggest that 5ARs may exert their anti-cancer effects by activating HCLS1 and suppressing TLR4/MYD88/NF-κB signaling, thus offering a potential new therapeutic strategy for CRC.